"Jetzt wächst zusammen, was zusammen gehört". (Willy Brandt, 10.11.1989) - RSCG, Butter, Rang; Foto Stephan Schraps ( stephan@schraps.com ); Sozialdemokratische Partei Deutschlands (SPD), Vorstand, Referat Öffentlichkeitsarbeit, Bonn; Courir-Druck, Bonn
Bemerkungen: Wandzeitung 19, 1989